Feasibility of Using Nanoparticles of SiO2 to Improve the Performance of Recycled Aggregate Concrete - Khaleel H. Younis; Shelan M. Mustafa (Advances in Materials Science and Engineering)
The aim of this paper was to examine the feasibility of using nanoparticles of SiO2 (nanosilica) to improve the performance of recycled aggregate concrete (RAC) containing recycled aggregate (RA) derived from processing construction and demolition waste of concrete buildings. The examined properties include compressive strength, splitting tensile strength, and water absorption. The study also includes examining the microstructure of RA and RAC with and without nanoparticles of SiO2. In total, nine mixes were investigated. Two mixes with RA contents of 50% and 100% were investigated and for each RA content; three mixes were prepared with three different nanoparticles dosages 0.4%, 0.8%, and 1.2% (by mass of cement). A control mix with natural aggregate (NA) was also prepared for comparison reasons. The results show that nanoparticles of silica can improve the compressive strength, tensile strength, reduce the water absorption, and modify the microstructure of RAC.